(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
On the basis of systematizing prior psychological developments of youthful period and growth of communication category status, psychological conditions and preconditions of communicative competence formation which are insufficiently concretized in the scientific literature are marked by the author of the article. In addition, psychological and pedagogical conditions assisting communicative competence formation of future economics teachers are defined.